Molecular identification of infectious bronchitis virus isolated from respiratory diseases in some Iranian broiler flocks - Ghorbiani, Mohsen (Mol Biol Rep, 2020)
Infectious Bronchitis (IB) is an acute, highly contagious disease associated with respiratory signs in young chickens and reduced egg production and quality in layers. The purpose of this study was to isolate and identify the infectious bronchitis virus in broiler flocks with respiratory diseases in four provinces of Iran. The specimens from forty IB suspected flocks from different regions of Isfahan, East Azerbaijan, Golestan, and Khuzestan provinces were collected, and the trachea, lung, and cecal tonsils were sampled. The samples were inoculated into 9- to 11-day—old embryonated chicken eggs. After collecting the allantoic fluid, RT-PCR was carried out to detect IB viruses. The results showed that IBVs were isolated from 30% of the flocks in these four provinces. The positive samples, according to a partial S1 gene sequence, were more investigated. Comparing nucleotide and amino acid sequences showed that the four isolates had the most similarity to the Pakistani 793/B strain (GI-13 lineage). The three isolates had the most considerable similarity in amino acid and nucleotide sequences to Iraqi and Iranian QX-like viruses (GI-19 lineage). Two isolates had 96 to 98% resemblance to Iranian variant-2 (GI-23 lineage) isolates. One isolate was found to belong to the Massachusetts serotype (GI-1 lineage) having 100% similarity in its amino acid sequence to the Massachusetts serotypes in GenBank. The phylogenetic relationship of the isolates shows complexity and diversity concerning different sequences and geographical regions.